Unlocking environmental harmony through export earnings: exploring the impact of remittances and infrastructure growth - Xiaoming Yi; Md Qamruzzaman (Frontiers in Environmental Science)
IntroductionThis study investigates the complex relationship between economic growth, remittances (REM), export earnings (EEs), infrastructural development (IFD), and environmental sustainability (ES) in Bangladesh over the period from 1990 to 2020. Framed within the context of the Environmental Kuznets Curve (EKC) hypothesis, the research explores how these factors influence environmental outcomes and contributes to ongoing discussions on sustainable development.MethodsUtilizing advanced time-series modeling techniques, including autoregressive distributed lag (ARDL) and nonlinear ARDL (NARDL), this study applies unit root tests and co-integration analysis to examine the data. These methods allow for a detailed assessment of both short- and long-term relationships between the variables in question.ResultsThe findings confirm the EKC hypothesis, showing that economic growth initially leads to increased carbon emissions and environmental degradation, but further development contributes to environmental improvements. Remittances, however, significantly exacerbate carbon emissions and ecological degradation. On the other hand, technological innovation (TI) demonstrates a negative association with carbon emissions and ecological footprint (EF), highlighting its potential in supporting sustainable development. The impacts of export earnings and infrastructural development on environmental sustainability are mixed, with infrastructural growth in particular linked to environmental degradation.DiscussionThe study's results underscore the importance of targeted policy interventions to balance economic growth with environmental sustainability. Policymakers should focus on mitigating the environmental impacts of remittance inflows and fostering technological innovation to achieve the Sustainable Development Goals (SDGs). While export earnings and infrastructural development play critical roles in economic progress, their environmental implications require careful management to ensure long-term sustainability.